The Criteria of Sustainable Product Development and Organizational Performance - Hj Mohd Akhir Hj Ahmad; Rosman Iteng; Rohaizah Saad; Mohd Kamarul Irwan Abd Rahim (International Journal of Supply Chain Management, 2018)
The demand for quality product has encouraged organizations to adopt the criteria of sustainable product development that can affect organizational performance. The objectives of developing sustainable product are to satisfy customers, achieve sustainability in business and meet stakeholders demand on the industry. Nevertheless, adopting the criteria of sustainable product in a new product development in industry is rarely present, especially in an automotive industry. This study addresses the relationship between the criteria of sustainable product development and the effect on an organizational performance. Thus, the outcome of this study contributes to the enhancement of criteria for sustainable product development in the automotive industry and other related industries. The causal relationship approach is adopted in this study by using random sampling among the 273 automotive suppliers in Malaysia. The analysis result using PLS SEM reveals that the criteria of sustainable product development that consists of economy, social and environment are contributing to significant positive effect on the organizational performance in automotive industry.